Ethical values in Islamic financial planning - Abdullah, Amalina; Muhammad, Junaina (Penerbit Universiti Kebangsaan Malaysia, 2013)
Muslims are encouraged to plan their lives economically and financially in order to achieve the objectives of Shariah (i.e. Maqasid As-Shariah). The intention to conduct Islamic financial planning must be aligned with the application of Maqasid As-Shariah, which emphasizes on the protection of essential needs of Muslims that include preservation of wealth. Financial planning provides direction and meaning for every financial decision. This study examines the basic theories, concepts and practices of Islamic financial planning and the emphasis of ethical conduct in financial planning. The practice of Islamic financial planning must be based on ethical values from Islamic theoretical framework.